2021
DOI: 10.1002/hpm.3176
|View full text |Cite
|
Sign up to set email alerts
|

Providers' perspectives on the performance of primary healthcare centres in India: The missing link

Abstract: Background: Primary healthcare centres (PHCs) form the foundation of the Indian public health system, and thus their effective functioning is paramount in ensuring the population's health. The World Health Organisation (WHO) has set six aspects of performance assessment for general health systems, which are hardly applicable to the PHC setup in a low-and middle-income country. The Primary Health Care Performance Initiative (PHCPI) has prescribed a framework with five domains consisting of 36 indicators for pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…There are several challenges in delivering primary healthcare in India, from patients’ and providers’ sides alike [ 28 , 29 ]. Digital health interventions show potential for the management of primary healthcare, particularly in rural and health access-limited areas of LMICs, including India [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several challenges in delivering primary healthcare in India, from patients’ and providers’ sides alike [ 28 , 29 ]. Digital health interventions show potential for the management of primary healthcare, particularly in rural and health access-limited areas of LMICs, including India [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 It is critical to include service users' and providers' perspectives when evaluating the quality of services. 7,8 Respecting the patient's needs, preferences, and being sensitive to aspects of care other than medical aids helps in providing patients centered care. 9 Studies have shown that all patient needs are interconnected, therefore, identifying these issues early and providing the necessary support can help alleviate the problems of patients to a large extent.…”
Section: Introductionmentioning
confidence: 99%